Development of a Novel Lipid-Based Nanosystem Functionalized with WGA for Enhanced Intracellular Drug Delivery - Gabriela Hädrich; Gustavo Richter Vaz; Juliana Bidone; Virginia Campello Yurgel; Helder Ferreira Teixeira; Alexandre Gonçalves Dal Bó; Luciano da Silva Pinto; Mariana Appel Hort; Daniela Fernandes Ramos; Antonio Sergio Varela Junior; Pedro Eduardo Almeida da Silva; Cristiana Lima Dora (MDPI AG, 2022)
Despite a considerable number of new antibiotics under going clinical trials, treatment of intracellular pathogens still represents a major pharmaceutical challenge. The use of lipid nanocarriers provides several advantages such as protection from compound degradation, increased bioavailability, and controlled and targeted drug release. Wheat germ agglutinin (WGA) is known to have its receptors on the alveolar epithelium and increase phagocytosis. The present study aimed to produce nanostructured lipid carriers with novel glycosylated amphiphilic employed to attach WGA on the surface of the nanocarriers to improve intracellular drug delivery. High-pressure homogenization was employed to prepare the lipid nanocarriers. In vitro, high-content analysis and flow cytometry assay was employed to study the increased uptake by macrophages when the nanocarriers were grafted with WGA. A lipid nanocarrier with surface-functionalized WGA protein (~200 nm, PDI > 0.3) was successfully produced and characterized. The system was loaded with a lipophilic model compound (quercetin; QU), demonstrating the ability to encapsulate a high amount of compound and release it in a controlled manner. The nanocarrier surface functionalization with the WGA protein increased the phagocytosis by macrophages. The system proposed here has characteristics to be further explored to treat intracellular pathogens.